Physical Hazards among Non-Healthcare Workers in Tertiary Hospitals in Rivers State - Etiobhio Etiobhio; Faith Ilosen; Onyeaso Onyeaso; Adedamola Olutoyin (Riviera Publishing, 2025)
Non-healthcare workers in tertiary hospitals in Rivers State face a range of physical hazards, including slips, trips, and falls; eye strain; headaches; fatigue; and more severe injuries like cuts, bruises, fractures, electrical shocks, and body pains, particularly in the neck, shoulders, and back. Therefore, it is crucial to identify, assess, and control these hazards to improve workplace safety, reduce absenteeism, and enhance overall productivity. This study adopted a cross-sectional survey design. A self-structured questionnaire titled